Television Economics - Beebe Jack H.; Manning Willard G. Jr; Owen Bruce M (Lexington Books, 1974)
Preface, Economics of Television Program Markets, Introduction, The Supply of Programming, Theories of Program Choice, The Behavior of Networks, Public Policy Toward Television, Improving Television Performance with Limited Channels, Improving Television Performance with Unlimited Channels, Public Television, Related Policy Issues, Bibliography, Index, About the Authors.